2016
DOI: 10.1111/jwas.12252
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility of Glandless Cottonseed Protein in Diets for Pacific White Shrimp, Litopenaeus vannamei

Abstract: Accurate digestibility coefficients for protein, energy, and lipid are needed by feed formulators to optimize diets to meet nutritional requirements and to substitute ingredients cost‐effectively. Of particular interest is protein, which accounts for the majority of shrimp feed content and expense. The current study evaluated seven cottonseed meal and protein products. Most of the samples were derived from a glandless cotton variety that lacks significant levels of the antinutritive compound, gossypol. The var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
2
6
0
Order By: Relevance
“…The AED represents the fractional sum of the ADC values including protein, lipids, and carbohydrates (Siccardi, 2006); hence, the AED of a diet typically decreases as fibre content increases and vice versa (Fang, Yu, Buentello, Zeng, & Davis, 2016) Lech and Reigh (2012), which is consistent with the high AED value of BY50. By shifting the manufacturing process of brewer's yeast, considerable improvements can be made especially for the protein content (Blieck et al, 2007).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The AED represents the fractional sum of the ADC values including protein, lipids, and carbohydrates (Siccardi, 2006); hence, the AED of a diet typically decreases as fibre content increases and vice versa (Fang, Yu, Buentello, Zeng, & Davis, 2016) Lech and Reigh (2012), which is consistent with the high AED value of BY50. By shifting the manufacturing process of brewer's yeast, considerable improvements can be made especially for the protein content (Blieck et al, 2007).…”
Section: Discussionsupporting
confidence: 58%
“…The AED represents the fractional sum of the ADC values including protein, lipids, and carbohydrates (Siccardi, ); hence, the AED of a diet typically decreases as fibre content increases and vice versa (Fang, Yu, Buentello, Zeng, & Davis, ). The fibre content (41 g/kg) of BY50 was relatively lower than previous results evaluated by Qiu and Davis () (62.7 g/kg) and Liu et al () (80 g/kg).…”
Section: Discussionmentioning
confidence: 99%
“…Ash content in feeds decreased proportionally along with increases in the rate of inclusion of amaranth and quinoa, an effect that can be explained by the greater ash content of fishmeal compared to these meals (Table 1). The energy contained in the diets was 160-170 MJ kg -1 , which is similar to the reported standards for shrimp feeds (between 87 and 180 MJ kg -1 with an average of 159 MJ kg -1 ) (Siccardi III 2006).…”
Section: Discussionsupporting
confidence: 83%
“…Usually, the cell walls of plant proteins are rich in crude fiber and ash and therefore difficult to be digested by shrimp. Previous studies demonstrated that the ADC D of shrimp to cottonseed meal was about 50%-55% and ADC Pro was about 57.6%-82.9% [ 66 , 67 ]. Besides, gossypol is a natural terpenoid found in the glands of cotton and would reduce the intestinal nutrient digestion and absorption of bony fish [ 68 ], which is often mediated by triggering intestinal inflammation and disrupting the intestinal structure [ 69 ].…”
Section: Discussionmentioning
confidence: 99%